Effectiveness of discharge planning in reducing readmissions in children with chronic diseases: A systematic review - Wati, Alfah Ratna; Huda, Mega Hasanul; Waluyanti, Fajar Tri; Nurhaeni, Nani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Discharge planning is an important process to ensure continuity of care after discharge from the hospital. This process helps reduce readmission rates, especially in children with chronic illnesses. Discharge planning can be a strategic approach to preventing readmissions by ensuring a smooth transition of care from the hospital to home. Purpose: To determine the effect of discharge planning in reducing readmissions in children with chronic diseases. Method: This study uses a systematic review approach with reference to the PRISMA guidelines. The articles analyzed came from the PubMed, SAGE, and ScienceDirect databases with a Randomized Controlled Trial (RCT) research design. A total of 4 (four) articles were selected based on inclusion criteria, discharge planning topics, focus on children with chronic diseases, and publications in the last 5 (five) years (2020-2024). Results: Comprehensive discharge planning significantly reduces readmission rates in children with chronic illness. Findings include that structured family education improves parental readiness to care for children and that social factors, such as parental literacy and household resource availability, influence discharge planning success. Case management provides superior outcomes in reducing readmission rates and improving patient quality of life. An as-needed follow-up approach is highly efficacious without compromising intervention effectiveness. Conclusion: Discharge planning is an effective intervention in reducing readmission rates and improving the quality of home care for children with chronic illness. Successful implementation requires integrated family education, social support, and case management. Adapting the intervention to account for social and cultural factors is also important to improve success across contexts. Keyword: Children With Chronic Illness; Discharge Planning; Readmission. Pendahuluan: Discharge planning adalah proses penting untuk memastikan kelanjutan perawatan pasien setelah keluar dari rumah sakit. Proses ini membantu mengurangi angka readmisi, terutama pada anak dengan penyakit kronis. Discharge planning dapat menjadi pendekatan strategis untuk mencegah readmisi dengan memastikan transisi perawatan yang lancar dari rumah sakit ke rumah. Tujuan: Untuk mengetahui efektivitas discharge planning dalam mengurangi readmisi pada anak dengan penyakit kronis. Metode: Penelitian systematic review mengacu pada panduan PRISMA. Artikel yang dianalisis berasal dari database PubMed, SAGE, dan ScienceDirect dengan desain penelitian Randomized Controlled Trial (RCT). Sebanyak 4 artikel dipilih berdasarkan kriteria inklusi, topik discharge planning, fokus pada anak dengan penyakit kronis, dan publikasi dalam 5 tahun terakhir (2020-2024). Hasil: Discharge planning yang komprehensif secara signifikan menurunkan angka readmisi pada anak dengan penyakit kronis. Temuan mencakup edukasi keluarga terstruktur meningkatkan kesiapan orang tua dalam merawat anak dan faktor sosial, seperti literasi orang tua dan ketersediaan sumber daya rumah tangga memengaruhi keberhasilan discharge planning. Manajemen kasus memberikan hasil superior dalam menurunkan angka rawat inap ulang dan meningkatkan kualitas hidup pasien. Pendekatan follow-up berbasis kebutuhan (as-needed) memiliki efisiensi tinggi tanpa mengurangi efektivitas intervensi. Simpulan: Discharge planning efektif dalam mengurangi angka readmisi dan meningkatkan kualitas perawatan di rumah bagi anak dengan penyakit kronis. Keberhasilan intervensi ini membutuhkan edukasi keluarga, dukungan sosial, dan manajemen kasus yang terintegrasi. Penyesuaian intervensi dengan mempertimbangkan faktor sosial dan kultural juga penting untuk meningkatkan keberhasilan di berbagai konteks. Kata Kunci: Anak-Anak dengan Penyakit Kronis; Readmisi; Rencana Pemulangan Pasien.